2019
DOI: 10.1038/s41598-019-43144-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk score has added value over initial clinical grading stage in predicting disease progression in age-related macular degeneration

Abstract: Several prediction models for progression of age-related macular degeneration (AMD) have been developed, but the added value of using genetic information in those models in addition to clinical characteristics is ambiguous. In this prospective cohort study, we explored the added value of genetics using a genetic risk score (GRS) based on 52 AMD-associated variants, in addition to the clinical severity grading at baseline as quantified by validated drusen detection software, to predict disease progression in 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…65 Another PRS comprising all 52 AMD-associated variants was applied to an independent prospective German cohort of AMD patients, and was associated with drusen load in agreement with earlier reports from the AREDS cohort. 66,67 Moreover, the 52-variant PRS was associated with drusen progression in individuals with low drusen load at baseline, and both drusen and AMD progression to late disease in those with intermediate drusen load during the mean 6.5 years of follow-up. 66 Seddon and Rosner 68 have incorporated 13 AMDassociated risk loci into a predictive model including known demographic and ocular risk factors (baseline AMD grading) in the AREDS cohort and further validated this in an independent longitudinal AMD cohort.…”
Section: Age-related Macular Degenerationmentioning
confidence: 93%
“…65 Another PRS comprising all 52 AMD-associated variants was applied to an independent prospective German cohort of AMD patients, and was associated with drusen load in agreement with earlier reports from the AREDS cohort. 66,67 Moreover, the 52-variant PRS was associated with drusen progression in individuals with low drusen load at baseline, and both drusen and AMD progression to late disease in those with intermediate drusen load during the mean 6.5 years of follow-up. 66 Seddon and Rosner 68 have incorporated 13 AMDassociated risk loci into a predictive model including known demographic and ocular risk factors (baseline AMD grading) in the AREDS cohort and further validated this in an independent longitudinal AMD cohort.…”
Section: Age-related Macular Degenerationmentioning
confidence: 93%
“…When individual drusen decrease in size, they may result in no residual anatomic defects or they may evolve into GA or nAMD . The total number of drusen or measured drusen area or volume, are risk factors for the progression to GA and nAMD . Also, the location of the drusen is of predictive value for disease progression, since eyes with drusen near the fovea have a higher probability of developing late AMD compared to eyes with drusen outside the fovea .…”
Section: Phenotypic Risk Factorsmentioning
confidence: 99%
“…In primary open-angle glaucoma, a higher PRS is associated with several endophenotypes, including earlier disease onset, intraocular pressure, and optic disc vertical cup-to-disc ratio [ 27 , 28 , 29 , 30 ]. However, few reports demonstrated the association of a PRS with endophenotypes in exudative AMD [ 11 ]. The present study demonstrated that PRSs can be informative in predicting the treatment response in the context of exudative AMD, though further studies are required to elucidate the exact relationship between such PRSs, and clinical features and treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Heesterbeek et al [ 11 ] demonstrated that a polygenic risk score (PRS) can contribute to predicting AMD progression ( n = 177). However, to date, no reports describe research investigating the relationship between PRS and treatment outcomes in the context of VEGF-inhibitor-based treatment of exudative AMD.…”
Section: Introductionmentioning
confidence: 99%